The last Tosa : Iwasa Katsumochi Matabei, bridge to Ukiyo-e - Kita, Sandy, 1950- (Honolulu : University of Hawaiì Press, 1999)
Iwasa Katsumochi Matabei (1578-1650) is one of the most controversial figures in Japanese art history. For more than half a century, historians have argued over Matabei's role in Japanese art: Was he, as he asserted, "The Last Tosa" (the school of painters who specialized in Yamato-e, a kind of classical courtly painting) or, as others characterized him, "The Founder of Ukiyo-e," the style of painting associated with the urban commoner class. In this highly original and convincing study, Matabei emerges as both - an artist in whose work can be seen elements of both Yamato-e and Ukiyo-e. Extending its analysis beyond the individual artist, The Last Tosa examines the trends and artistic developments of a transitional period and makes heretofore unexamined connections between the world of the aristocrat and the merchant as well as the two artistic schools that reflected their tastes
pt. I. The problem. The learned gentleman. A gentleman of low repute. Commoner style. Courtly subject matter -- pt. II. Matabei as machishu. The many faces of the machishu. Defining Matabei, 1578-1615. Machishu subject matter. Style revisited -- pt. III. The last tosa as founder of Ukiyo-e. Echizen and Edo: Matabei's life, 1617-1650. The chonin painter. The last tosa. App. II. Matabei's travel diary.
Includes bibliographical references (pages 397-402) and index.
Print version record.
JSTOR
Keywords: Iwasa, Matabē, -- 1578-1650.; Iwasa, Matabē, -- 1578-1650.; Iwasa, Matabē, -- 1578-1650; Painters -- Japan -- Biography; Ukiyoe; Peintres -- Japon -- Biographies; Ukiyo-e.; Ukiyo-e.; BIOGRAPHY & AUTOBIOGRAPHY -- Artists, Architects, Photographers; ART -- History -- General; ART -- Asian; Painters; Ukiyoe; Japan; Humaniora -- Kunst; Biographies